Family composition, income, and healthy diet in rural China: evidence from three provinces - Yang, Minda; Amar, Nimra; Zhao, Longqiang; Pan, Cong (Frontiers in Nutrition, 2025)
A healthy diet is essential for public health and plays a central role in sustainable food systems. This paper investigates the impact of family composition and income on dietary health within rural households in China, analyzing how these factors correlate with dietary diversity and quality. Utilizing a 3-day food consumption record data across three provinces, we apply ordinary least squares regression to explore the relationships with three key dietary health indicators: the Entropy Index of dietary diversity (E), the Chinese Food Pagoda Score (CFPS), and the Chinese Healthy Eating Index (CHEI). Our findings indicate that higher household income significantly improves all measures of dietary health, affirming the critical role of economic factors in achieving a nutritious diet. In contrast, a higher proportion of elderly individuals within households is associated with poorer dietary outcomes, suggesting specific challenges in meeting the nutritional needs of aging populations. These findings offer insights into how demographic and income factors shape dietary practices, contributing to discussions on sustainable food consumption in developing regions. This research contributes to the understanding of dietary health dynamics in rural China and supports broader efforts to attain sustainable development goals related to health and wellbeing.